2008
DOI: 10.1179/174328908x283285
|View full text |Cite
|
Sign up to set email alerts
|

Energy management in plastics processing — framework for measurement, assessment and prediction

Abstract: Energy management is a task of growing importance to plastics processors but there is no established structure for measurement, assessment and prediction. Many companies are trying to measure the wrong things in the wrong ways. They then wonder why they get the wrong answers! This paper describes and illustrates a framework for measurement, assessment and prediction that can be used for most plastics processing companies. It looks at both internal and external benchmarking, at site level and at machine level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…It is observed from Figure 12 a decrease in the SEC as the phr of leather residues increases, the same behavior was observed in Ref. 37 where the torque value is influenced by the shape and size of the filler, reflected in the SEC variation.…”
Section: Resultssupporting
confidence: 69%
“…It is observed from Figure 12 a decrease in the SEC as the phr of leather residues increases, the same behavior was observed in Ref. 37 where the torque value is influenced by the shape and size of the filler, reflected in the SEC variation.…”
Section: Resultssupporting
confidence: 69%
“…4, corresponds to each analyzed machine from Table 1 and they are an average of five cycles analyzed. The same behavior presented in other studies was observed (R. Kent 2008b). When the machine output rises, the SEC drops.…”
Section: Resultssupporting
confidence: 89%
“…The SEC is correlated with the production volume (Iwko and Steller 2018;Thiriez and Gutowski 2006). The most complete and welldocumented study of external benchmarking of injection molding machines was published by Kent (D. R. Kent 2008a;R. Kent 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…In processes, VP printers use significantly less energy than FFF printers, even when post-processing is included. However, both AM technologies require significantly higher energy consumption values than injection molding and polymer extrusion [109]. Figure 18 shows the range of energy consumption values found for each printer category used in the study by Hopkins et al [20], compared to reported values for injection molding and extrusion [20,109].…”
Section: Discussionmentioning
confidence: 98%